The principle of self-determination in homeschooling students according to Ki Hajar Dewantara's Perspective - Alfariza, Syafira; Bektiarso, Singgih; Prihandono, Trapsilo (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
The principle of self-determination is an important concept in education that emphasises independence, freedom, and individual responsibility for the learning process. In the context of homeschooling, this principle provides opportunities for students to manage learning according to their interests, talents, and needs. Ki Hajar Dewantara's perspective, which emphasises ‘Ing Ngarsa Sung Tuladha, Ing Madya Mangun Karsa, Tut Wuri Handayani,’ becomes the philosophical foundation in developing student-centred homeschooling education. This philosophy supports freedom of learning without overriding the role of educators as guides and companions. This article examines how the principle of self-determination is applied to homeschooling students in Ki Hajar Dewantara's perspective, including aspects of learning independence, the role of parents as educators, and the importance of building an educational ecosystem that supports students' potential holistically. The results of the analysis show that the application of this principle can increase students' intrinsic motivation, creativity, and responsibility in the learning process, in line with the goals of national education to create independent and characterised human beings.